2005
DOI: 10.1111/j.1467-789x.2005.00176.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of overweight and obesity prevalence in school‐aged youth from 34 countries and their relationships with physical activity and dietary patterns

Abstract: The purposes of this systematic review were to present and compare recent estimates of the prevalence of overweight and obesity in school-aged youth from 34 countries and to examine associations between overweight and selected dietary and physical activity patterns. Data consisted of a cross-sectional survey of 137 593 youth (10-16 years) from the 34 (primarily European) participating countries of the 2001-2002 Health Behaviour in School-Aged Children Study. The prevalence of overweight and obesity was determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

87
717
24
75

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 970 publications
(903 citation statements)
references
References 27 publications
87
717
24
75
Order By: Relevance
“…Lobstein and Frelut (2003), who examined data using the IOTF cutoff points based on measured weight and height of 7 to 11-year-old children from 21 European countries, showed that prevalence of OW in France is similar to levels observed in northern European countries (12-22%), and much lower than those observed in southern Europe, mainly Spain (34%) or Italy (36%). Another review by Janssen et al (2005), based on reported body measurements of 10 to 16-year-old schoolchildren from 34 European countries also based on IOTF cutoff points, ranked France in an intermediary position with levels close to those observed in northern countries (10-15%), higher than levels in eastern Europe (o10%) and lower than levels observed in Great Britain, Spain, Italy and Greece (15-20%). This review also suggested that French 10 to 16-year-old schoolchildren spend less time watching TV and using the computer than this age group in other European countries.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Lobstein and Frelut (2003), who examined data using the IOTF cutoff points based on measured weight and height of 7 to 11-year-old children from 21 European countries, showed that prevalence of OW in France is similar to levels observed in northern European countries (12-22%), and much lower than those observed in southern Europe, mainly Spain (34%) or Italy (36%). Another review by Janssen et al (2005), based on reported body measurements of 10 to 16-year-old schoolchildren from 34 European countries also based on IOTF cutoff points, ranked France in an intermediary position with levels close to those observed in northern countries (10-15%), higher than levels in eastern Europe (o10%) and lower than levels observed in Great Britain, Spain, Italy and Greece (15-20%). This review also suggested that French 10 to 16-year-old schoolchildren spend less time watching TV and using the computer than this age group in other European countries.…”
Section: Discussionmentioning
confidence: 98%
“…It confirms that childhood OW prevalence is high in France, as already suggested by three recent national surveys, each on a narrower age range. These showed prevalence rates of OW (including obesity) of 14.5% in children aged 5-6 years (1999-2000) (Labeyrie and Niel, 2003), 18.1% in children aged 7-9 years (2000) (Rolland-Cachera et al, 2002), 20.0% in preadolescents aged 10-11 years (2001-2002) (Labeyrie and Niel, 2004), and 11.6% in adolescents aged 11-16 years (2001-2002) (Janssen et al, 2005), with respect to the same IOTF definition (Cole et al, 2000). Lastly, the results of the ObEpi (Obesity Epidemiology), another national survey performed in 2000 on a larger sample of children aged 2-17 years, but which did not account for behavioural risk factors, gave 13.3% (Basdevant and Guy-Grand, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 In addition, while cross-sectional data on screen time in 10-16 year olds from 34 countries showed higher degrees of overweight with increased TV viewing in 65% of the countries, this leaves more than one-third having no association. 10 Overall, therefore, sedentary behavior in the form of screen time is implicated in youth overweight and obesity, but findings are less clear cut than some claim.…”
Section: Contextmentioning
confidence: 99%
“…These studies have investigated the influence of lifestyle determinants on childhood overweight (e.g. lifestyle factors (3)(4)(5)(6)(7)(8)(9) ), but only few studies have addressed …”
mentioning
confidence: 99%